Site characterization in karst and pseudo-karst terraines : practical strategies and technology for practicing engineers, hydrologists and geologists /: practical strategies and technology for practicing engineers, hydrologists and geologists. ([2015]) - Benson, Richard C; Yuhr, Lynn B
No abstract available